Intra- and Perioperative Complications with the Minimally Invasive Antero-lateral Approach (OLIF) to the Lumbar Spine. Issue 1 (April 2016) - Mehren, Christoph; Sauer, Daniel; Siepe, Christoph; Mayer, Michael; Korge, Andreas
Introduction: Anterior lumbar fusion is a common treatment option for a variety of pathologies. In the last years minimally invasive anterior approach techniques are considered standard. One of them, the extreme lateral transpsoas approach (XLIF) has become popular in the last years. Within this XLIF-approach neuromonitoring is considered mandatory to avoid neurological complications. An alternative lateral, oblique, psoas-sparing approach has been described in 1997. This approach, recently named OLIF (oblique lumbar interbody fusion), has been routine in our center over 15 years. The aim of the study was to evaluate the rate of intraoperative and perioperative complications of this antero-lateral ante psoas approach. Material and Methods: A retrospective chart review was performed in a consecutive series of 812 patients who underwent minimally invasive anterolateral lumbar fusion in our institution between 1998 and 2010. Each patients record was reviewed by an independent observer. Patients demographics, diagnosis, co-morbidities, operative procedures, levels of surgery, operating time, intra- and perioperative complications etc. were analyzed. Results: All patients were operated through a left-sided minimally invasive retroperitoneal oblique approach (OLIF) between L1 and L5. Indications for surgery were DDD, vertical and translational instabilities, tumor, fracture and revision surgeries. The mean age of patients was 61.5 years (16–88; 317 females, 495 males). Surgery was performed in 1205 levels and 62.3% were single level ( n  = 506) procedures. In the majority of the cases OLIF was part of a 360° fusion either dorsoventral ( n  = 729) or ventrodorsal ( n  = 65). In 18 cases a stand-alone anterior procedure was performed. Operating time averaged 110 minute. (range 30–410 minute) including the multilevel cases. The overall complication rate in direct relationship to the OLIF approach was 3.7% (30/812). The access-related intraoperative complications consisted of 3 vascular injuries (0.37%) and 3 radicular sensomotoric deficits (0.37%). In 6 cases (0.74%) we observed sensoric deficits combined with pain as donorside morbidity while harvesting a tricortical bone block out out the anterior iliac crest within the same approach. There were no abdominal or urological injuries. In the early postoperative period we experienced 2 superficial (0.24%) and 3 deep (0.37%) wound infections, 5 superficial (0.62%) and 6 deep (0.74%) hematomas. In 2 cases a postoperative paralytic ileus occurred. Conclusion: This retrospective study reports about the access-related intraoperative complications of a large series of OLIF cases of the levels L1-L5 performed in a single center through a standardized left sided approach. The risk of neurolgical complications seems to be significantly lower compared with what is described with the extreme lateral transpsoas approach (XLIF). The risk of vascular, abdominal or urogenital injuries is low. There was no necessity for intraoperative neuromonitoring nor was there a necessity for a vascular surgeon. The OLIF is an easy and safe appoach for anterior lumbar interbody fusion from L1-L5 for a variety of pathologies.